Extra high temperature coefficient in semiconducting BaTiO3-(Bi0.5Na0.5)TiO3-SrTiO3 ceramics. Issue 2 (1st February 2019) - Yan, Liang; Fu, Qiuyun; Zhou, Dongxiang; Wang, Mei; Zu, Hao; Wang, Geng; Zheng, Zhiping; Luo, Wei
Abstract: Sr is often doped on the Ba-site of ferroelectric perovskite BaTiO3 -based PTC ceramics to move the Curie point of BaTiO3 from ~ 120 °C to a lower value for special applications. However, the addition of Sr often decreases their temperature coefficients. Although many methods were adopted to improve it, the temperature coefficient is still under 25%. In this paper, we introduced a small amount x of (Bi0.5 Na0.5 )TiO3 into BaTiO3 -SrTiO3 PTC ceramics. As a result, the temperature coefficient of (1-x) (BaTiO3 -SrTiO3 )-x(Bi0.5 Na0.5 )TiO3 ceramics reached an extra high value ~ 38.3% at x = 0.02 and meanwhile its room temperature resistivity was still a practical value of ~ 555.7 Ω cm. The maximum temperature coefficient reached up to ~ 54.0% at x = 0.03 and the corresponding room temperature resistivity was ~ 4930.2 Ω cm. The shift of the Curie point caused by the addition of BNT can be easily offset because that its amount was small. The excellent temperature coefficient was attributed to the weakened relaxation behavior induced by addition of BNT.